Fabrication and structural optimization of porous single-crystal α-Fe2O3 microrices for high-performance lithium-ion battery anodes1. Issue 32 (28th August 2015) - Yu, Bao Zhi; Liu, Xiao Li; Zhang, Hui Gang; Jing, Guang Yin; Ma, Pei; Luo, Yane; Xue, Wei Ming; Ren, Zhao Yu; Fan, Hai Ming
<x xml:space="preserve">Abstract</x> Porous α-Fe2O3 microrices have been prepared as a model system to study the effect of structural optimization of porous microstructures on LIB performance.